2018
DOI: 10.1101/491365
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DEEPScreen: High Performance Drug-Target Interaction Prediction with Convolutional Neural Networks Using 2-D Structural Compound Representations

Abstract: The identification of physical interactions between drug candidate chemical substances and target biomolecules is an important step in the process of drug discovery, where the standard procedure is the systematic screening of chemical compounds against pre-selected target proteins. However, experimental screening procedures are expensive and time consuming, therefore, it is not possible to carry out comprehensive tests. Within the last decade, computational approaches have been developed with the objective of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…This means accurate and efficient computational prioritization of novel synergistic drug pair candidates will keep being an important research area. In MatchMaker, we use only the drug chemical structure as the primary feature, which has been used in parallel tasks such as drug target identification [50] or drug side effect prediction [51,52]. We also use the cell line specific gene expression profile to capture the context of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…This means accurate and efficient computational prioritization of novel synergistic drug pair candidates will keep being an important research area. In MatchMaker, we use only the drug chemical structure as the primary feature, which has been used in parallel tasks such as drug target identification [50] or drug side effect prediction [51,52]. We also use the cell line specific gene expression profile to capture the context of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…tions, to simultaneously predict interactions between multiple protein targets and multiple candidate ligands or drugs (16)(17)(18)(19)(20). DTI models use the experimental data available for some subset of interactions ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, images and CNNs have been used to predict drug–protein interactions and outperformed models trained on flattened versions of the images, which cannot exploit the spatial structure. 31…”
Section: Introductionmentioning
confidence: 99%
“…These authors found that augmenting the same deep-learning architecture with only three additional chemical properties further improved model performance, suggesting that chemical images alone may not entirely capture the important characteristics of a chemical. Finally, images and CNNs have been used to predict drug–protein interactions and outperformed models trained on flattened versions of the images, which cannot exploit the spatial structure …”
Section: Introductionmentioning
confidence: 99%